Cloud hunting: doryphagy, a form of selective autophagy that degrades centriolar satellites. Issue 2 (1st February 2020) - Holdgaard, Søs Grønbæk; Cianfanelli, Valentina; Cecconi, Francesco
ABSTRACT: The selective clearance of cellular components by macroautophagy (hereafter autophagy) is critical for maintaining cellular homeostasis. In this punctum, we summarize and discuss our recent findings regarding a novel type of selective autophagy that targets centriolar satellites (CS) for degradation, a process we termed doryphagy from the Greek word "doryphoros", standing for "satellite". CS are microtubule-associated protein complexes that regulate centrosome composition. We show that CS degradation is mediated through a direct interaction between GABARAPs and an LC3-interacting region (LIR) motif in the CS protein PCM1. Autophagy-deficient systems accumulate large abnormal CS and consequently display centrosome reorganization and abnormal mitoses. Our findings provide a mechanistic link between autophagy deficiency and centrosome abnormalities and exemplify how mammalian Atg8-family proteins (mATG8s) can regulate substrate specificity.